Agronomic efficiency of nano-integrated nutrient management on cotton yield traits under arid farming conditions - Israilov, Inomjon; Sindarov, Obidjon; Salomov, Shavkat; Khayitov, Kholmurod; Bobokulov, Shoxnazar; Begmatov, Ilkhom; Isabaev, Khasimbek; Uspankulov, Bekjan; Khasanova, Odinakhon; Tungushova, Dilbar; Turakulov, Dilmurod; Karimova, Komola; et al. (Frontiers in Sustainable Food Systems, 2025)
Cotton (Gossypium spp.) is a globally cultivated climate resilience fiber crop known for its potential to produce substantial biomass and yield in stress environments. However, its production requires a huge amount of chemicals, bringing harm to the environment and ecosystem services. Field studies during the 2023–2024 growing seasons were focused on agronomic parameters of cotton in response to nano (Si and Uzbi) and three chemical fertilizer regimes (N150 P105 K75; N200P140 K100; N250P175K125) under arid condition of Uzbekistan. The experiment was arranged in a split-plot design with three replications. The application of nano Si improved nutrients uptake and yield parameters of cotton under open-field arid environment due to a positive synergism between nano and chemical fertilization. The effect of Si nano compound was more pronounced at the lower fertilizer regime (N150P105K75), exhibiting the increase of cotton yield by 31.3% and 1000 seed weight by 5.32% than those in the control. On the other hand, the Uzbi treatment exhibited high efficacy at the intermediate fertilizer level (N200P140K100), enhancing total cotton biomass by 12.9% and total yield by 26.3% relative to the control. The Si nano was found to be relatively efficient in terms of NUE, crop yield and may help reduce the reliance on excessive chemicals in current climate changing scenario. This study explored the cost-effective pathways toward more sustainable cotton production through the synergistic combination of nano and chemical fertilizers in irrigated arid agricultural regions.